2018
DOI: 10.1073/pnas.1808535115
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for antibiotic resistance mediated by the Bacillus subtilis ABCF ATPase VmlR

Abstract: SignificanceThe recent increase in multidrug-resistant pathogenic bacteria is limiting the utility of our current arsenal of clinically important antibiotics. The development of improved antibiotics would therefore benefit from a better understanding of the current resistance mechanisms employed by bacteria. Many Gram-positive bacteria, including pathogenic Staphylococcus aureus and Enterococcus faecalis, utilize ribosome protection proteins to confer resistance to medically relevant antibiotics, such as strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
227
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(268 citation statements)
references
References 43 publications
24
227
2
Order By: Relevance
“…B. subtilis and E. coli strains (Crowe-McAuliffe et al, 2018;Guerout-Fleury et al, 1996;Guerout-Fleury et al, 1995;Horinouchi and Weisblum, 1982;Murina et al, 2019;Takada et al, 2014) used in this study are listed in Table S3. All B. subtilis strains used were derivatives of the wild-type 168 strain.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…B. subtilis and E. coli strains (Crowe-McAuliffe et al, 2018;Guerout-Fleury et al, 1996;Guerout-Fleury et al, 1995;Horinouchi and Weisblum, 1982;Murina et al, 2019;Takada et al, 2014) used in this study are listed in Table S3. All B. subtilis strains used were derivatives of the wild-type 168 strain.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Here again, one of the ATP molecules could be used to reset of the system after the protein has identified the ribosomes inhibited by the antibiotic. To be sure, experimental evidence has established that antibiotic resistance ABC-F proteins reset the peptidyl transferase centre of the ribosome to counter translational arrest (Crowe-McAuliffe et al, 2018;Murina et al, 2018).…”
Section: Accurate Template Recognition During Translation and Antibiomentioning
confidence: 99%
“…Based on the complex model, ABC1 and ABC2 of SrpA established massive interactions with ribosomal protein and the elbow of the P-tRNA, while the interdomain linker, especially the extended loop region, projected deep into the ribosome PTC, interacted with the CCA arm of P-tRNA, and was located in proximity to 23S rRNA helices H89 and H73. The architecture and conformation of the SrpAribosome interactions were very similar to those of MsrE/VmlR, suggesting that the binding site of antibiotic resistance ABC-F proteins is highly conserved [23,24]. Valnemulin-ribosome docked compounds revealed that the tricyclic mutilin core on the base of C2452, U2505, U2506, A2062, G2061, and its C14 extension was stabilized by U2585 [2,13,14].…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have demonstrated that antibiotic resistance ABC-F proteins bind to the ribosome and allosterically dissociate the drug from its binding site [23,24]. In the present work, molecular docking was used to analyze SrpA-ribosome interactions.…”
Section: Homology Modeling and Molecular Docking Of Srpamentioning
confidence: 99%
See 1 more Smart Citation